Recent status and challenges in multifunctional electrocatalysis based on 2D MXenes. Issue 14 (1st July 2022) - Ponnada, Srikanth; Kiai, Maryam Sadat; Gorle, Demudu Babu; Bose, Rapaka S. C.; Rajagopal, Venkatachalam; Saini, Bhagirath; Kathiresan, Murugavel; Nowduri, Annapurna; Singhal, Rahul; Marken, Frank; Kulandainathan, Manickam Anbu; Nanda, Karuna Kar; et al.
Abstract : This review throws light on the development and emerging electrocatalytic applications of potentially important 2D material MXene with specific references to oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER). Abstract : Due to their chemical and electrical characteristics, such as metallic conductivity, redox-activity in transition metals, high hydrophilicity, and adjustable surface properties, MXenes are emerging as important contributors to oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) catalyst development. In this review, we summarize current advances in electrocatalysis using MXene-based composite materials for the ORR, OER, and HER, and their linking processes to theoretical models. Significant factors that affect the properties of MXene based electrocatalysts, including functional groups, conductivity, and interfacial design, are discussed. Recent advances in MXene material engineering and material technology are also discussed. Finally, we have discussed the current limitations of ORR, OER, and HER electrocatalysts based on MXene composites, obstacles to their future development, and recommendations for future research efforts.